A new approach to delineating clinical target volume for radiotherapy of glioblastoma: A phase II trial - Huang, Yong; Ding, Haixia; Luo, Min; Li, Zhiqiang; Li, Sirui; Xie, Conghua; Zhong, Yahua (Frontiers in Oncology, 2022)
Purpose No consensus has currently been reached regarding the optimal radiation volume for radiotherapy of glioblastoma. Here, we have proposed a new delineation approach to delineating clinical target volume based on the relationship between the growth patterns of glioblastoma and neural pathways. Its safety and efficacy were evaluated in a phase II clinical trial. Methods A total of 69 patients with histologically confirmed glioblastoma were enrolled. All patients underwent tumor resection, followed by focal radiotherapy and concomitant temozolomide (TMZ), and then received six cycles of adjuvant TMZ. The gross tumor volume (GTV) was defined as the surgical resection cavity plus any residual enhancing tumor, on contrast enhanced T1-weighted MRI. The clinical target volume (CTV) was delineated through our new approach. Results The median recurrence-free survival (RFS) and overall survival (OS) were 11.4 months and 18.2 months, which were better than the previous reports. Relapse was found in 47 patients, of whom 41 patients (87.2%) failed in central, two patients (4.3%) failed in field, and four patients (8.5%) failed in distance. No marginal recurrence was found. Our regimen showed a trend of lower rates of marginal recurrence, and the brain volume of high-dose radiation fields in our regimen was similar to that of EORTC (p = 0.257). Conclusions We have proposed a novel method for the delineation of clinical target volume by referencing the nerve fiber bundles for radiotherapy of glioblastoma. The results of the present phase II clinical trial suggest that this approach may be feasible and effective.